Volumetric of the lateral ventricles in computed tomography images in Cubans adults with normal cognitive functions - Katherine S. Hernandez-Cortés; Adrián A. Mesa-Pujals; Nelsa M. Sagaró del Campo; Montoya Pedrón-Arquímedes (Revista Mexicana de Neurociencia, 2023)
Introduction: The use of morphometric methods based on neuroimaging to determine brain volumetric related to aging for clinical diagnosis has been largely restricted to high-resolution imaging techniques. Texture, as a method of image analysis, has shown promising results in the detection of visible and non-visible lesions, and that in computerized axial tomography studies they are scarce. Objective: The objective of the study was to evaluate the effect of normal aging on the volume of the lateral ventricles, estimated from single-slice computed tomography (CT) imaging techniques, using an automatic processing method of homogeneous texture indices. Methodology: An observational and analytical study was developed in 320 subjects with normal neurocognitive functions and neuropsychiatric examination, aged between 30 and 75 years and over, who underwent a single-slice Computed Axial Tomography of the skull. An image segmentation method based on homogeneity was used. Results: The analysis of variance showed that advancing age is associated with a proportional increase in the volume of the lateral ventricles. Conclusions: The morphometric method of the lateral ventricles developed from CT/homogeneity segmentation images, allows to quantify the cerebral volumetric changes associated with normal aging and can be used as a biomarker of cerebral atrophy.